The Interleukin 13 receptor system : a novel pathomechanism involved in pulmonary arterial hypertension - Hecker, Matthias; Justus Liebig University Giessen (My University, 2008)
Idiopathic pulmonary arterial hypertension (IPAH) is characterized by medial hypertrophy and pulmonary artery smooth muscle cell (paSMC) proliferation in pulmonary arteries. Interleukin (IL)-13 is a potent regulator of tissue fibrosis and remodeling, and its effects are dependent on the cell-type specific expression of the IL-13 receptor isotypes IL-4Ralpha, IL-13Ralpha1, and IL-13Ralpha2. This study analyzed the expression of the IL-13 receptors in IPAH in vivo and paSMC ex vivo, and the effects of IL-13 stimulation on paSMC proliferation and apoptosis. Using quantitative RT-PCR and immunohistochemistry, we detected an increased expression of IL-13Ralpha2, but not IL-4Ralpha, or IL-13Ralpha1, in lungs of IPAH patients compared with controls (transplant donors). Similar results were obtained in lungs of mice subjected to chronic hypoxia-induced pulmonary hypertension or rats exposed to monocrotaline. Immunohistochemistry and laser-captured microdissection analysis further demonstrated a strong localization of IL-13Ralpha2 to paSMC. Functional analysis using freshly isolated paSMC revealed that IL-13 induced a dose-dependent growth inhibition, without inducing apoptotic effects. This anti-proliferative effect of IL-13 was due to G0/G1 cell cycle arrest and phosphorylation of STAT3 and STAT6 in paSMC. Finally, ectopic overexpression of IL-13Ralpha2 in primary paSMC attenuated the anti-proliferative effect exerted by IL-13, and diminished IL-13-induced STAT3 and 6 phosphorylation. Our studies thus demonstrate that IL-13 is a potent anti-proliferative regulator of paSMC. Up-regulation of the decoy receptor IL-13Ralpha2 on paSMC in IPAH leads to a loss of this anti-proliferative effect and therefore enhanced paSMC proliferation during the pathogenesis of the disease.Furthermore, microarray analysis revealed that IL-13 induced a massive downregulation of the pro-proliferative endothelin-1 in paSMC, a finding that was also confirmed on protein level. Thus, the described anti-proliferative effect of IL-13 on paSMC might be mediated by a downregulation of endothelin-1.

Idiopathische pulmonale Hypertonie (IPAH) ist charakterisiert durch eine Mediahypertrophie und Proliferation der pulmonalen glatten Gefäßmuskelzellen (paSMC). Interleukin-13 (IL-13) ist ein potenter Regulator von Gewebefibrose mit entsprechenden Umbauprozessen (remodeling) und seine biologischen Effekte sind abhängig vom zelltypspezifischen Expressionsmusters der IL-13 Rezeptor Isotypen IL-4Ralpha, IL-13Ralpha1 und IL-13Ralpha2. In der vorliegenden Studie untersuchten wir die Expression der IL-13 Rezeptoren in Proben von Lungen, entnommen von IPAH Patienten, in vivo und paSMC ex vivo und ferner die Effekte der IL-13 Stimulation auf die Proliferation und Apoptose von paSMC.Mittels quantitativer RT-PCR und Immunohistochemie konnten wir eine verstärkte Expression von IL-13Ralpha2, nicht aber von IL-4Ralpha und IL-13Ralpha1, in Lungen von IPAH-Patienten im Vergleich zu Kontrollpatienten detektieren. Ähnliche Resultate konnten in Lungen von Mäusen mit durch chronischer Hypoxie ausgelöster pulmonaler Hypertonie und dem Monokrotalin-Rattenmodell beobachtet werden. Untersuchungen mittels Immunhistochemie und Laser-gestützter Mikrodissektion zeigten weiterhin eine starke Lokalisation von IL-13Ralpha2 in paSMC. Funktionelle Analysen an frisch isolieren paSMC zeigten, dass IL-13 eine dosis-abhängige Inhibition des Zellwachstums ohne apoptotische Effekte induziert. Dieser anti-proliferative Effekt von IL-13 beruhte auf einem Stopp des Zellzyklus in der G0/G1-Phase und einer Phosphorylierung von STAT3 und STAT6 in paSMC. Überexpression von IL-13Ralpha2 führte zu einer signifikanten Abnahme der IL-13 induzierten Wachshemmung und verringerte die zuvor beobachtete Phosphorylierung von STAT3 und STAT6. Weiterführende Microarray-Untersuchungen zeigten u.a., dass IL-13 zu einer stark reduzierten Genexpression des pro-proliferativen Endothelin-1 in paSMC führt. Unsere Studie zeigt, dass IL-13 ein potenter anti-proliferativer Regulator des paSMC-Wachstums ist, was durch eine IL-13-induzierte Minderexpression von Endothelin-1 erklärt werden kann. Verstärkte Expression von IL-13Ralpha2 auf paSMC von IPAH Patienten führt zu einem Verlust dieses anti-proliferativen Effekts und deshalb einer gesteigerten Proliferation der paSMC im Verlauf der Erkrankung.
Das Interleukin 13 Rezeptor System : ein neuer Pathomechanismus des Lungenhochdrucks
Keywords: PAH; PAH; ddc:610